FAKTOR-FAKTOR EKONOMI YANG MEMPENGARUHI USAHA KERAJINAN GENTENG DI DESA PEJATEN KABUPATEN TABANAN - Satya Ariantha, Gede Agus; Utama, Made Suyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023, 2023)
Industrial development is one part of the implementation of regional development in Bali. The idea of ??developing the industrial sector, especially the tile industry in the Tabanan area, Kediri District, precisely in Pejaten Village, can be seen as a very strategic and rational effort considering that this business is very interesting in making tiles typical of Pejaten Village. The purpose of this study was to analyze the effect of capital, raw materials, labor simultaneously and partially on the production of tile craftsmen in Pejaten Village and to analyze the economic scale of tile craftsmen's business in Pejaten Village. The data used in this study is primary data, with a sample of 29 tile craftsmen. The analysis technique used is multiple linear regression analysis. The results showed that simultaneously capital, raw materials, and labor had an effect on the production of tile craftsmen in Pejaten Village. Partially, capital and labor have a positive and significant effect, while raw materials have a positive and insignificant effect on the production of tile craftsmen in Pejaten Village. The value of the economic scale of the tile craftsman business in Pejaten Village shows that they are in a decreasing return to scale condition.